Factors Affecting Visual Prognosis of Myopic Foveoschisis after Macular Buckling - Xiujuan Zhao; Yanbing Wang; Yuqing Chen; Silvia Tanumiharjo; Yijin Wu; Ping Lian; Shida Chen; Xia Huang; Bingqian Liu; Lin Lu (Journal of Ophthalmology)
Purpose. To analyze the visual prognosis of macular buckling in patients with high myopia foveoschisis (FS) and to identify factors that predict the final visual outcome. Methods. We retrospectively included 155 eyes of 155 patients who underwent foveoschisis-related macular buckling. Best-corrected visual acuity (BCVA) and coexisting macular pathologies were assessed as a measure of surgical outcome, and multivariate linear regression was performed to identify factors affecting final visual prognosis. Results. The mean preoperative BCVA was 1.19 ± 0.55 logMAR (20/308), while the mean postoperative BCVA was 0.82 ± 0.51 logMAR (20/133) (P<0.001). Anatomical success was achieved in 151/155 eyes (97.42%) after the first surgery and in 155/155 eyes (100%) at the 2-year follow-up visit. Both preoperative and postoperative BCVA were better in eyes without macular hole (MH) than in eyes with MH. In patients with MH, the postoperative BCVA was significantly better than that before surgery when the MH was closed. However, the difference was not significant in patients with unclosed MH. Univariate analysis identified that baseline BCVA, age, MH, atrophic myopic maculopathy category, and postoperative intraretinal cyst were significantly related to BCVA at the postoperative 2-year follow-up. Multivariate analysis revealed that preoperative BCVA and age were significant factors. Conclusion. Better preoperative BCVA and younger age are predictors of better prognosis. Prompt surgery is advised for patients with myopic foveoschisis to improve their visual prognosis.